Multilevel Analysis on Factors Affecting Measles Rubella Immunization Uptake among Toddlers in Pekanbaru, Indonesia - Rosadi, Wahyuni; Sulaeman, Endang Sutisna; Prasetya, Hanung (Journal of Maternal and Child Health, 2019)
Background: Measles-Rubella (MR) immunization is a way to prevent measles and rubella, because the disease cannot be treated and the treatment given to patients is only supportive. Measles and rubella are spread in almost all provinces in Indonesia, so it needs a high and evenly coverage of at least 95% to break the chain of transmission. This study aimed to analyze the determinants of MR immunization uptake in infants. Subjects and Method: This was a cross-sectional study conducted in 25 community health posts (posyandu) in Pekanbaru, Indonesia, from April to May 2019. A sample of 200 mothers who had children aged 9-59 months was selected by stratified random sampling. The dependent variable was Rubella-Measles immunization. The independent variables were maternal education, maternal knowledge, family support, perceived susceptibility, perceived severity, perceived benefit, perceived barrier, cues to action, and self-efficacy. The data were collected by questionnaire and analyzed by a multilevel multiple logistic regression. Results: Measles-Rubella immunization uptake increased with high maternal education (b= 0.66; 95% CI= -0.07 to 1.41; p= 0.080), high maternal knowledge (b= 0.90; 95% CI= 0.14 to 1.65; p= 0.020), strong family support (b= 0.71; 95% CI= -0.05 to 1.48; p= 0.068), high perceived susceptibility (b= 1.24; 95% CI= 0.33 to 2.14; p= 0.007), high perceived severity (b= 1.19; 95% CI= 0.36 to 2.03; p= 0.005), strong perceived benefit (b= 0.93; 95% CI= 0.19 to 1.66; p= 0.013), high cues to action (b= 0.96; 95% CI= 0.19 to 1.73; p= 0.014), and high self efficacy (b= 1.45; 95% CI= 0.59 to 2.31; p= 0.001). It decreased with strong perceived barrier (b= -1.05; 95% CI= -1.81 to -0.29; p= 0.007). Posyandu had a contextual effect on Rubella-Measles immunization with ICC= 10.53%. Conclusion: Measles-Rubella immunization uptake increases with high maternal education, high maternal knowledge, strong family support, high perceived susceptibility, high perceived severity, strong perceived benefit, high cues to action, and high self efficacy. It decreases with strong perceived barrier. Posyandu has a contextual effect on Rubella-Measles immunization. Keywords: Measles, Rubella, immunization, health belief model, multilevel analysis Correspondence: Wahyuni Rosadi. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: wahyuni.rosadi08@gmail.com. Mobile: 085271819193. Journal of Maternal and Child Health (2019), 4(6): 448-460 https://doi.org/10.26911/thejmch.2019.04.06.06